Validity assessment of MNA among an elderly population in Kerala,South India. - Shilpa Jose and Kumari K.S (International Journal of Advanced Research, 2014)
Statistics point to the fact that the central challenge of the growing elderly population is indeed their health. A growing body of evidence suggests that there are nutritional components to many of the health problems and preventive nutrition strategies may play a significant role in chronic conditions which do affect independence, quality of life and health care expenditure.Though anthropometric and biochemical measurements are usually performed to define the type and severity of malnutrition, there is no generally accepted ‘gold standard’ for diagnosis of geriatric malnutrition .In this context the present study was carried out with the following specific objectives as to define the nutritional status of the elderly using a comprehensive approach including anthropometry, biochemical and clinical assessments . Also a global tool for assessment of nutritional status of elderly,the Mini Nutritional Assessment (MNA) tool was also used. Using clinical status of subjects as ‘gold standard’, the MNA demonstrated a sensitivity of 90.2% percent and specificity of 96.4% percent in identifying well nourished and malnourished elderly, which is excellent. Use of BMI as a ‘gold standard’ also showed that MNA had excellent sensitivity (95.4 %) and specificity (93.9%) in identifying malnutrition. It was concluded that MNA is able to classify the elderly as well nourished and malnourished with reasonable accuracy. The feasibility of use of the MNA tool in routine geriatric assessments in the study region is acceptable and MNA is there for recommended for use in the study region.